The Stroop Task Influences Product Evaluations - Damen, Tom G. E. (Frontiers in Psychology, 2021)
Cognitive conflict is considered to represent a psychologically negative signal. Indeed, a recent publication by Damen, Strick, Taris, and Aarts (2018) showed that cognitive conflict emerging from the Stroop task influences evaluations for neutral shapes that had become associated with conflict and non-conflict respectively. Building on these findings, the present research investigates the degree to which Stroop conflict influences evaluations of actual products. In an experimental study, participants performed a Stroop task in which they responded to conflict trials (e.g., the word red presented in a blue font) as well as non-conflict trials (e.g., the word red presented in a red font). Participants were also presented with two pictures featuring bottled water brands: One brand was consistently presented after non-conflict trials, the other brand was consistently presented after conflict trials. When participants evaluated the products, the results showed they rated the product associated with Stroop conflict less favorably than the product associated with non-conflict, however this effect only emerged when participants were thirsty. When participants were not thirsty, no differences emerged. The present findings: - Add to the literature of an emerging research line that explores the link between cognitive conflict and negativity; - Provide a partial extension of a previous result, in that the negativity emerging from the Stroop conflict task negatively influences the evaluations of associated stimuli; - Show that Stroop conflict influences evaluations of relevant products - consumer items - not just meaningless and abstract stimuli; - Highlight the importance of product relevance for the relation between Stroop conflict and product evaluations.